SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN KENAIKAN JABATAN DI PT.PUPUK KUJANG CIKAMPEK METODE FUZZY MAMDANI (Information Technology and Telematics, 2013)
Selection of employees in accordance with the criteria contained in a certain position, so if there is a position on a blank part of the company's employees are needed to fill it. In this case the analysis needs to be done to the employees according to the calculations fit the job criteria. Objectives to be achieved is to build a model of decision support system that can be used to conduct the election office at PT. Kujang Cikampek using Mamdani Fuzzy method. This research has resulted in a decision support system that can be made to support PT. Kujang Cikampek to do with the selection criteria of office of education, discipline, loyalty, communication, and problem solving and results using Fuzzy Mamdani inference. Keyword: SPK, PT. Kujang Cikampek, Mamdani Fuzzy